2020
DOI: 10.1111/1462-2920.15015
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genomic characterization of a new ‘Candidatus Nitrotoga’ isolate

Abstract: Summary Oxidation of nitrite to nitrate is an important process in the global nitrogen cycle. Recent molecular biology‐based studies have revealed that the widespread nitrite‐oxidizing bacteria (NOB) belonging to the genus ‘Candidatus Nitrotoga’ may be highly important for the environment. However, the insufficient availability of pure Nitrotoga cultures has limited our understanding of their physiological and genomic characteristics. Here, we isolated the ‘Ca. Nitrotoga’ sp. strain AM1P, from a previously enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 60 publications
3
47
0
Order By: Relevance
“…Across the entire genus, physiology data have only been reported for a small number of Ca. Nitrotoga cultures, which were enriched from permafrost, activated sludge, an aquaculture system, and coastal sand (Alawi et al, 2007(Alawi et al, , 2009Hüpeden et al, 2016;Ishii et al, 2017Ishii et al, , 2020Kitzinger et al, 2018;Wegen et al, 2019). These physiological studies have indicated that optimal temperatures for Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Across the entire genus, physiology data have only been reported for a small number of Ca. Nitrotoga cultures, which were enriched from permafrost, activated sludge, an aquaculture system, and coastal sand (Alawi et al, 2007(Alawi et al, , 2009Hüpeden et al, 2016;Ishii et al, 2017Ishii et al, , 2020Kitzinger et al, 2018;Wegen et al, 2019). These physiological studies have indicated that optimal temperatures for Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the broad distribution of Ca . Nitrotoga in freshwater systems and beyond, only six genomes are available, derived from rivers heavily impacted by urban and agricultural influence, a wastewater treatment plant, and coastal sediment (30,77,78). Hence the metabolic and phylogenetic diversity of this group is virtually unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrotoga including NtogaGL1a/b encode similar electron transport pathways, including NADH dehydrogenase-Complex I, succinate dehydrogenase-Complex II, and Alternative Complex III, along with high-affinity cbb3-type cytochrome oxidases suggesting adaptation to low oxygen conditions. They also share the Calvin cycle for carbon fixation, a complete TCA cycle, and an evolutionarily distinct nitrite oxidoreductase (NXR) from other NOB (30,77,78). All Ca .…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation rates were often measured to evaluate the optimum temperature of NOB pure cultures (Nowka et al, 2015b;Kitzinger et al, 2018). The cell number and the amount of oxidized nitrite showed a good positive correlation (Nowka et al, 2015a;Ushiki et al, 2017;Ishii et al, 2020). The culture experiment for determining the generation time (see below) showed that the isolated cells grew exponentially 2-4 days after nitrite addition.…”
Section: Physiological Activity Test To Determine Optimum Temperaturementioning
confidence: 99%
“…To investigate the generation time, the isolate was incubated at 28 • C after replacing the supernatant in order to remove the nitrate and by-products by centrifugation. Nitrite and nitrate concentrations were measured using the ion chromatography with a TSKgel SuperIC-Anion HS (IC-2010; Tosoh, Tokyo, Japan) according to the protocol described in our previous studies (Fujitani et al, 2020;Ishii et al, 2020). Cell numbers were estimated by performing qPCR analysis of the nxrB gene as described in a previous study (Ushiki et al, 2017).…”
Section: Physiological Activity Test To Determine Optimum Temperaturementioning
confidence: 99%